Effect of Performance Deficiencies on Graduation and Board Certification Rates: A 10-yr Multicenter Study of Anesthesiology Residents. Issue 6 (December 2016) - Turner, Judi A.; Fitzsimons, Michael G.; Pardo, Manuel C.; Hawkins, Joy L.; Huang, Yue Ming; Rudolph, Maria D.; Keyes, Mary A.; Howard-Quijano, Kimberly J.; Naim, Natale Z.; Buckley, Jack C.; Grogan, Tristan R.; Steadman, Randolph H.
Abstract : (Abstracted from Anesthesiology, 125:221–229, 2016) The authors of this retrospective study sought to determine how deficiencies in resident performance affect graduation and board certification. Data regarding resident performance over a 10-year period, taken from 4 academic anesthesiology residencies, served as the basis for the study.